The student jargon in the Diccionario de autoridades - Gómez-Pablos, Beatriz (Romanica Olomucensia, 2014)
The student jargon, characterized by the changing nature of the community that uses it, has been studied mainly from the second half of the twentieth century. Despite of having a long history of centuries, there is still a lack of studies of earlier times. This paper is aimed to place the first stone in the reconstruction of student jargon and to cover a part of the deficit. This has made a complete emptying of the voices and expressions contained in the Diccionario de Autoridades (1726-1739), identified from the lexicographical signs offered in the articles.
Keywords: student jargon; Diccionario de Autoridades; lexicography; metalexicography; 18th century.